Specification of Sprouty2 functions in osteogenesis in in vivo context - Vesela, Barbora (Organogenesis, 2019)
Sprouty proteins are modulators of the MAPK/ERK pathway. Amongst these, Sprouty2 (SPRY2) has been investigated as a possible factor that takes part in the initial phases of osteogenesis. However, the in vivo context has not yet been investigated and the underlying mechanisms taking place in vitro remain unknown. Therefore, in this study, the impact of Spry2 deficiency was examined in the developing tibias of Spry2 deficient (-/-) mouse. The investigation was performed when the osteogenic zone became clearly visible and when all three basic bone cells types were present. The main markers of osteoblasts, osteocytes and osteoclasts were evaluated by immunohistochemistry and RT-PCR. RT-PCR showed that the expression of Sost was 3.5 times higher in Spry2-/- than in the wild-type bone, which pointed to a still unknown mechanism of action of SPRY2 on the differentiation of osteocytes. The up-regulation of Sost was independent of Hif-1α expression and could not be related to its positive regulator, Runx2, since none of these factors showed an increased expression in the bone of Spry2-/- mice. Regarding the RANK/RANKL/OPG pathway, the Spry2-/- showed an increased expression of Rank, but no significant change in the expression of Rankl and Opg. Thanks to these results, the impact of Spry2 deletion is shown for the first time in the developing bone as a complex organ including, particularly, an effect on osteoblasts (Runx2) and osteocytes (Sost). This might explain the previously reported decrease in bone formation in postnatal Spry2-/- mice.